NEP 2020 in Terms of Physical Education and Sports Science: A Comprehensive Analysis - Mr. Naru Katara; Dr. Vishnubhai D. Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The National Education Policy (NEP) 2020 of India represents a significant shift in the country's approach to education. This research paper examines the implications of NEP 2020 for physical education and sports science in India. Through a comprehensive analysis of the policy document, relevant literature, and expert opinions, this study explores the potential impact of NEP 2020 on curriculum development, teacher training, infrastructure, and overall sports culture in educational institutions. The findings suggest that while NEP 2020 provides a promising framework for integrating physical education and sports science into the mainstream curriculum, significant challenges remain in terms of implementation and resource allocation. This paper contributes to the ongoing discourse on education reform in India and provides valuable insights for policymakers, educators, and researchers in the field of physical education and sports science.
Keywords: NEP 2020; physical education; sports science; curriculum development; teacher training; sports infrastructure